Dinamika Alih Fungsi Lahan Pertanian di Tengah Tekanan Urbanisasi dan Pembangunan Ekonomi: Sebuah Kajian Bibliometrik Sistematis - Ris Setya Resa; Indah Susilowati; Hastarini Dwi Atmanti (SAFE-Network, 2026)
Agricultural land conversion to built-up areas represents one of the most fundamental structural challenges in contemporary development economics, particularly in rapidly urbanizing developing countries. This study maps the global scientific landscape on agricultural land conversion from an economic perspective, through a systematic bibliometric analysis of 239 Scopus-indexed articles published between 2008 and 2026, screened from 3,209 initial records accessed on 1 June 2026 at 11:41 AM WIB. Methods include co-citation analysis, keyword co-occurrence mapping, author and country collaboration network analysis, and research theme evolution mapping using VOSviewer. Results reveal a significant surge in publications since 2019, peaking in 2025 (46 articles). Four major thematic clusters were identified: (1) agricultural land conversion and food security, (2) urbanization and spatial planning, (3) land policy and sustainable development, and (4) landscape and climate change. China and Indonesia emerged as active research hubs, while South-South collaboration remains limited. These findings imply the need for more integrated interdisciplinary approaches connecting economics, public policy, and natural resource governance in addressing agricultural land conversion threats to food security and long-term economic development.